2019
DOI: 10.1084/jem.20181812
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Salmonella trehalose phospholipids reveals functional convergence with mycobacteria

Abstract: Salmonella species are among the world’s most prevalent pathogens. Because the cell wall interfaces with the host, we designed a lipidomics approach to reveal pathogen-specific cell wall compounds. Among the molecules differentially expressed between Salmonella Paratyphi and S. Typhi, we focused on lipids that are enriched in S. Typhi, because it causes typhoid fever. We discovered a previously unknown family of trehalose phospholipids, 6,6′-diphosphatidyltrehalose (diPT) and 6-phosphatidyltrehalose (PT). Card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 57 publications
(78 reference statements)
1
35
0
Order By: Relevance
“…TDM is also partly responsible for the low permeability of the mycobacterial cell wall, which consequently confers drug resistance [ 30 ]. Recently, the trehalose phospholipids 6,6,-diphosphatidyltrehalose (diPT) and 6-phosphatidyltrehalose (PT) have been discovered in a group of related gram-negative bacteria which includes some Salmonella and Escherichia isolates [ 31 ]. Like TDM, diPT is a symmetrical molecule with a trehalose core and lipids attached at the 6-positions, and it is a ligand for macrophage inducible Ca2-dependent lectin receptor (Mincle) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TDM is also partly responsible for the low permeability of the mycobacterial cell wall, which consequently confers drug resistance [ 30 ]. Recently, the trehalose phospholipids 6,6,-diphosphatidyltrehalose (diPT) and 6-phosphatidyltrehalose (PT) have been discovered in a group of related gram-negative bacteria which includes some Salmonella and Escherichia isolates [ 31 ]. Like TDM, diPT is a symmetrical molecule with a trehalose core and lipids attached at the 6-positions, and it is a ligand for macrophage inducible Ca2-dependent lectin receptor (Mincle) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the trehalose phospholipids 6,6,-diphosphatidyltrehalose (diPT) and 6-phosphatidyltrehalose (PT) have been discovered in a group of related gram-negative bacteria which includes some Salmonella and Escherichia isolates [ 31 ]. Like TDM, diPT is a symmetrical molecule with a trehalose core and lipids attached at the 6-positions, and it is a ligand for macrophage inducible Ca2-dependent lectin receptor (Mincle) [ 31 ]. However, the roles of diPT and PT in disease are yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The strong structural analogies of these newly discovered molecules with TDM led to immunological studies, which showed that diPT is similarly potent as a Mincle ligand and thus can serve as a new candidate for adjuvant development. 15…”
mentioning
confidence: 99%
“…Next, Reinink et al (2019) investigated how trehalose phospholipids are synthesized in Salmonella . By considering PT and diPT as carbohydrate-substituted phosphatidylglycerols, bioinformatic analysis identified 12 genes that are potentially involved in the biosynthesis of these molecules.…”
mentioning
confidence: 99%
“…Accurate annotation of multigene families (where multiple family members are present in the same genome) is particularly challenging since the enzymes in these families often undertake similar chemistry on closely related substrates (Zallot et al, 2016). With this in mind, it is perhaps unsurprising that the trehalose phospholipid synthase identified by Reinink et al (2019) was originally annotated as a cardiolipin synthase. Nonetheless, the observation that S. Typhi clsB does not appear to encode a cardiolipin synthase should prompt a thorough analysis of the genes annotated as such, since this aspect of lipid biosynthesis is evidently more nuanced than its annotations suggest.…”
mentioning
confidence: 99%